2017
DOI: 10.1155/2017/3494289
|View full text |Cite
|
Sign up to set email alerts
|

FOXO Transcriptional Factors and Long‐Term Living

Abstract: Several pathologies such as neurodegeneration and cancer are associated with aging, which is affected by many genetic and environmental factors. Healthy aging conceives human longevity, possibly due to carrying the defensive genes. For instance, FOXO (forkhead box O) genes determine human longevity. FOXO transcription factors are involved in the regulation of longevity phenomenon via insulin and insulin-like growth factor signaling. Only one FOXO gene (FOXO DAF-16) exists in invertebrates, while four FOXO gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 102 publications
(123 reference statements)
4
97
0
Order By: Relevance
“…Hence, we found that up-regulation of TCF19 enhances the G1/S phase transition in HCC cells. Increasing studies have also established that FOXO1 is involved in diverse cellular pathways; including proliferation, stress resistance, differentiation and apoptosis [23]. Deregulation of FOXO1 has been found in many cancers, including prostate cancer, leukemia and melanoma [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we found that up-regulation of TCF19 enhances the G1/S phase transition in HCC cells. Increasing studies have also established that FOXO1 is involved in diverse cellular pathways; including proliferation, stress resistance, differentiation and apoptosis [23]. Deregulation of FOXO1 has been found in many cancers, including prostate cancer, leukemia and melanoma [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed the transcription factor family, FOXO, impacts cell growth, proliferation, differentiation, and longevity (Murtaza et al, ). FOXO transcription factors act to integrate cellular signals of insulin, growth factors, cytokines, and oxidative stress (Klotz et al, ; Myatt, Brosens, & Lam, ; Tzivion et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed the transcription factor family, FOXO, impacts cell growth, proliferation, differentiation, and longevity (Murtaza et al, 2017). AKT, a serine/threonine-specific protein kinase that phosphorylate many of its downstream targets to regulate cell metabolism, also phosphorylates FOXO3α at Threonine 32, Serine 253, and Serine 315 residues (Tzivion et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forkhead box O (FOXO) transcription factors are critical players that modulate the expression of genes involved in growth, stress resistance, neurological diseases, cancer, and metabolism (Coomans de Brachene & Demoulin, ; Fluteau et al., ; Murtaza et al., ). Drosophila possesses one FOXO factor, whereas human has FOXO1,3,4, and 6, among which FOXO1 and FOXO3 are the main isoforms (Webb & Brunet, ).…”
Section: Introductionmentioning
confidence: 99%